Analisis Pengukuran Kinerja Perusahaan Asuransi Dengan Konsep Balanced Scorecard (Studi Kasus Pada PT. BRILife Syariah Cabang Gatot Subroto) - Manik, M. Bay Hakqi; Rahma, Tri Inda Fadhila; Harahap, Muhammad Ikhsan (Jurnal Manajemen Akuntansi (JUMSI), 2024)
The Balanced Scorecard is a process that allows companies to evaluate strategies based on four perspectives. The purpose of this study to determine the effect of measuring the company's performance with the concept of balance scorecard using financial perspective, customer perspective, internal business perspective and growth and learning perspective of PT. BRILife Syariah Branch Gatot Subroto. This research is a quantitative research, and the source of data obtained is secondary data using annual financial statements in accordance with the variables used during the period (2019-2020). Population as many as 50 respondents customers and 35 respondents employees at PT. BRILife Syariah Branch Gatot Subroto. Using multiple linear regression analysis, with the results that the financial perspective persial effect on performance measurement, customer perspective has no effect on performance measurement, internal business perspective has no effect on performance measurement and growth and learning perspective has no effect on performance measurement. So that the financial perspective, customer perspective, internal business perspective and growth and learning perspectives simultaneously affect performance measurement. With a coefficient of determination (R square) of 1,000% which means financial perspective, customer perspective, internal business perspective and growth and learning perspective can explain 100% of the performance measurement of BRILife Syariah Gatot Subroto Branch.